Diversity in the Outdoors: National Outdoor Leadership School Students' Attitudes About Wilderness. (June 2017) - Gress, Sara; Hall, Troy
Outdoor experiential education (OEE) programs often cater to white, upper-class individuals. With major demographic shifts occurring in the United States, OEE organizations are confronting this imbalance. The National Outdoor Leadership School (NOLS) is addressing this issue with its Gateway Scholarship Program. The purpose of this mixed-methods study was to determine whether Gateway Scholarship and non-scholarship students held different wilderness attitudes and whether those attitudes changed following NOLS courses. A quantitative posttest and retrospective pretest was administered online ( n = 74), with follow-up telephone interviews ( n = 19). Results showed that Gateway students held less positive pre-course wilderness attitudes than non-Gateway students, but most post-course scores had converged. Both groups experienced positive change in wilderness attitudes. Interview data revealed potential reasons for attitude change and areas of possible concern about the conceptualization of wilderness promoted by NOLS.